Synthesis, Characterization of Some New 1,2,4-Triazole derivatives as Antimicrobial and Study of their Molecular docking - Damdoom, Wasan. K.; Al-Jeilawi, Oday H. R. (Iraqi Journal of Science, 2025)
This study outlines the synthesis of substituted 1,2,4-triazole derivatives through the cyclization reaction of thiourea derivatives. The process begins with the reaction of different halides with KSCN to produce isothiocyanate derivatives. then followed by a reaction with isonicotinic acid hydrazide to yield thioureas (1-6), with a yield rate of (72-88%). Then, compounds (1-6) were treated with alkaline medium 4 N (NaOH) to produced 1,2,4-triazole derivatives (7-12) with a yield (51-69%).The structure of the prepared compounds was characterized using FTIR,1HNMR and 13CNMR spectroscopy. Some of the synthesized compounds were tested for antimicrobial activity when, compound 9 showed strong activity against gram positive bacteria (Staphylococcus aureus, Staphylococcus epidermidis) and moderate activity against gram negative bacteria (Escherichia coli, Klebsiella pneumoniae) compared with drug ciprofloxacin. Also, examined compounds showed strong inhibition against (candida albicans) except compound 10 showed weak activity. Furthermore, the molecular docking was studied by Gold suite to examining the reaction between target compounds and active binding section of GABA-AT protein was the PLP fitness values of the docking compounds on GABA-AT ranged (57.71-67.55).